Monogenic diabetes in adults: A multi-ancestry study reveals strong disparities in diagnosis rates and clinical presentation. (June 2022) - Mifsud, F.; Saint-Martin, C.; Dubois-Laforgue, D.; Bouvet, D.; Timsit, J.; Bellanné-Chantelot, C.; ,
Abstract: Aim: Identification of monogenic diabetes (MgD) conveys benefits for patients' care. Algorithms for selecting the patients to be genetically tested have been established in EuroCaucasians, but not in non-EuroCaucasian individuals. We assessed the diagnosis rate, the phenotype of MgD, and the relevance of selection criteria, according to ancestry in patients referred for a suspected MgD. Methods: Seven genes ( GCK, HNF1A, HNF4A, HNF1B, ABCC8, KCNJ11, INS ) were analyzed in 1975 adult probands (42% non-EuroCaucasians), selected on the absence of diabetes autoantibodies and ≥2 of the following criteria: age ≤40 years and body mass index <30 kg/m 2 at diagnosis, and a family history of diabetes in ≥2 generations. Results: Pathogenic/likely pathogenic variants were identified in 6.2% of non-EuroCaucasian and 23.6% of EuroCaucasian patients (OR 0.21, [0.16–0.29]). Diagnosis rate was low in all non-EuroCaucasian subgroups (4.1–11.8%). Common causes of MgD ( GCK, HNF1A, HNF4A ), but not rare causes, were less frequent in non-EuroCaucasians than in EuroCaucasians (4.1%, vs. 21.1%, OR 0.16 [0.11–0.23]). Using ethnicity-specific body mass index cutoffs increased the diagnosis rate in several non-EuroCaucasian subgroups. Conclusion: The diagnosis rate of MgD is low in non-EuroCaucasian patients, but may be improved by tailoring selection criteria according to patients'ancestry.